The effect of length of free-surface gated circular conduit on air-demand ratio and aeration efficiency - Ozkan, Fahri; Demirel, Ibrahim Halil; Tuna, Muhammed Cihat; Baylar, Ahmet (Iwa Publishing, 2015)
Aeration is the process of bringing water and air into close contact in order to increase dissolved oxygen concentration. The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. The hydraulic structures can be accepted as the key components in increasing dissolved oxygen concentration because of the strong turbulent mixing associated with substantial air bubble entrainment at these structures. Closed conduit is a classic example of a hydraulic structure where aeration occurs. This work focused on determining the effect of conduit length on air-demand ratio and aeration efficiency in free-surface gated circular conduits. Experimental results showed that the Froude number had an important effect on the air-demand ratio and the aeration efficiency. The effect of the conduit length on the air-demand ratio and the aeration efficiency changed depending on the Froude number. It was demonstrated from the results that a free-surface gated circular conduit flow system had high efficiency in transferring oxygen from air bubbles to water. Moreover, a formula for the aeration efficiency was presented relating the aeration efficiency to the conduit length and the Froude number.
Keywords: aeration efficiency; air-demand ratio; conduit; free-surface flow; oxygen transfer